Методика расчета критических режимов течения в решетках аэродинамических профилей - Дорошенко, Е. В.; Терещенко, Ю. Ю.; Техрани, А. (НТУ "ХПИ", 2014)
В работе представлена разработанная методика расчета критических режимов «запирания» течения в решетках аэродинамических профилей с учетом вязкости. Предложены зависимости для расчета течения в межлопаточных каналах с учетом пограничного слоя для больших положительных и отрицательных углов атаки. Методика апробирована путем сопоставления известных экспериментальных данных и полученных авторами результатов численного эксперимента.

Aerodynamic calculation of axial compressor stages begins with a calculation of the air flow in the elementary steps, which are modeled by airfoil cascades. The aerodynamic characteristics of the compressor cascades are used in calculating the characteristics of the axial compressor stages and determining specific restrictions of its operation modes. The main limitations of operation modes of the compressor stage include restrictions at large positive angles of attack and the choking regimes of compressor stages by air flow rate. The occurrence of separation is the result of viscous-inviscid interaction of the flow layers, both viscous and non-viscous processes should be accurately simulated for its prediction. Herewith, it is necessary to take into account that they interact nonlinearly. The calculation method of the critical regimes of flow “chocking” in airfoil cascades considering viscosity was presented in the paper. Dependences for the calculation of critical flow regimes taking into account the boundary layer for large positive and negative angles of attack were proposed. The method was tested by comparing the known experimental data and the results of numerical experiment, obtained by the authors. Comparison of the calculated characteristics of “chocking” regimes for airfoil cascades with the experimental data indicates sufficient correctness of the proposed calculation method. The results of numerical experiment show that accounting real gas flow parameters in calculating the aerodynamic characteristics of the compressor cascades allows more reliably determine “chocking” border of blade channels by air flow rate.
Calculation method of critical flow regimes at the airfoil cascade
Keywords: запирание; моделирование; срыв; пограничный слой; компрессор; вязкость; сжимаемость; method; chocking; flow; cascade; simulation; stall; boundary layer; compressor; viscosity; compressibility